Adaptability and High School Students’ Online Learning During COVID-19: A Job Demands-Resources Perspective - Martin, Andrew J.; Collie, Rebecca J.; Nagy, Robin P. (Frontiers in Psychology, 2021)
The present study investigated the role of adaptability in helping high school students navigate their online learning during a period of COVID-19 that entailed fully or partially remote online learning. Drawing on Job Demands-Resources (JD-R) theory and data from a sample of 1,548 Australian high school students in 9 schools, we examined the role of adaptability in predicting students’ online learning self-efficacy in mathematics and their end of year mathematics achievement. It was found that beyond the effects of online learning demands, online and parental learning support, and background attributes, adaptability was significantly associated with higher levels of online learning self-efficacy and with gains in later achievement; online learning self-efficacy was also significantly associated with gains in achievement—and significantly mediated the relationship between adaptability and achievement. These findings confirm the role of adaptability as an important personal resource that can help students in their online learning, including through periods of remote instruction, such as during COVID-19.